Level of maternal respiratory syncytial virus (RSV) F antibodies in hospitalized children and correlates of protection. (August 2021) - Taleb, Sara A.; Al-Ansari, Khalid; Nasrallah, Gheyath K.; Elrayess, Mohamed A.; Al-Thani, Asmaa A.; Derrien-Colemyn, Alexandrine; Ruckwardt, Tracy J.; Graham, Barney S.; Yassine, Hadi M.
Highlights: This study found that 14% of maternal antibodies were present in infants at hospitalization. An average log2 EP titer of 10.2 was directed to both F-protein conformations. The neutralizing activity in infants was greater than that of binding antibodies. One-third of infants had relatively high NAb titers, yet, they were hospitalized. Abstract: Background: Respiratory syncytial virus (RSV) is a major cause of lower respiratory infection among children and no vaccine is available. The stabilized form of the fusion (F) protein – pre-F – is a leading vaccine candidate to target different populations, including pregnant women. This study aimed to determine the magnitude and nature of RSV-directed maternal antibodies (matAbs) in hospitalized children with RSV infection. Methods: Sixty-five paired blood samples were collected from RSV-infected children aged <6 months and their corresponding mothers. All pairs were screened for levels of pre-F and post-F antibodies using ELISA. The neutralizing antibodies (NAbs) in both groups were measured in vitro against mKate RSV-A2 using H28 cells. Results: It was found that 14% of matAbs (log2 12.8) were present in infants at hospitalization, with an average log2 EP titer of 10.2 directed to both F-protein conformations. Additionally, 61.4% of maternal NAbs (log2 EC50  = 9.4) were detected in infants (log2 EC50  = 8.7), which were mostly pre-F exclusive (81%). Pre-F antibodies in children showed a positive correlation with matAbs titers and negative correlations with age and bronchiolitis score. Conclusions: The maintenance of neutralizing activity in infants relative to maternal titers was greater than the maintenance of antibody binding based on ELISA, suggesting that higher-potency antibodies may have a longer half-life than weakly neutralizing antibodies.